Design of Literacy and Numeracy Learning Website for Elementary School Students Using the OOAD Approach - Ayu Tri Wardani Wardani; Alifya NFH (Fakultas Teknik Universitas Negeri Makassar, 2026)
This study designed an integrated web-based learning platform for literacy and numeracy that supports multiuser roles (students, teachers, and administrators) through interactive content, gamification, contextual assessment, and real-time learning analytics. This research and development study employed the object-oriented analysis and design (OOAD) methodology, focusing specifically on the micro process stages (identifying elements, defining collaborations, defining relationships, and detailing semantics). Data were collected through interviews with elementary school teachers, documentation of curriculum and learning materials, and literature studies. The study successfully produced a comprehensive system design featuring an integrated platform with learning content modules, gamification (games), interactive assessments with detailed question management, student progress tracking, and a teacher dashboard for learning analytics. The design includes a complete UML model, database structure, and modular 3-Tier MVC architecture that ensures scalability and maintainability. This study offers a novel contribution by providing a holistic, integrated OOAD-based website design specifically for elementary literacy and numeracy education in the Indonesian context. Unlike previous standalone digital media, this system combines gamification, contextual assessment with detailed question handling, and real-time analytics within a single modular platform.